1994
DOI: 10.5014/ajot.48.9.810
|View full text |Cite
|
Sign up to set email alerts
|

Motor Learning and Occupational Therapy: The Organization of Practice

Abstract: This article addresses implications for the practice of occupational therapy when that therapy is guided by theories of motor learning. In occupational therapy, clients must learn or relearn motor skills through the use of activities. The occupational therapist must present activities in a manner that elicits the retention and transfer of the desired skills for use in functional settings. Therefore, the therapist should strive for acquisition conditions that facilitate retention and transfer of the learned ski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 48 publications
1
16
0
2
Order By: Relevance
“…Additionally, the outcome measures are not based on the tasks used during training. The random practice findings in the present study complement other research (Jarus, 1994;Zwicker & Harris, 2009) that has reported better translation of motor control to novel tasks better than block practice. A functional outcome measure that would assess the application of learned movement may better represent changes in the random group.…”
Section: Discussionsupporting
confidence: 89%
“…Additionally, the outcome measures are not based on the tasks used during training. The random practice findings in the present study complement other research (Jarus, 1994;Zwicker & Harris, 2009) that has reported better translation of motor control to novel tasks better than block practice. A functional outcome measure that would assess the application of learned movement may better represent changes in the random group.…”
Section: Discussionsupporting
confidence: 89%
“…6a suggests that typing on the ergonomic configuration provided keyboarders with a learning opportunity that improved their overall performance on the standard configuration. This observation is supported by the motor learning theory of process specificity which suggests that if a individual practices on task in which the superficial conditions differ, but the underlying processes are unaffected, this may improve performance (Jarus, 1994;Schmidt and Lee, 1999). The ergonomic configuration may have provided enough variability for most standard keyboard users, that typing on it improved their standard keyboard performance, whereas typing on a standard configuration did not provide variability that could improve ergonomic keyboard performance.…”
Section: Article In Pressmentioning
confidence: 78%
“…La moitié des participants ont acquis une tâche complexe et l'autre moitié, une tâche simple. For occupational therapy, where the client must learn or relearn motor skills and perform them efficiently later, the acquisition conditions that produce optimal retention of the learned skills should be emphasized (Jarus, 1994). Les résultats indiquent que les participants s'étant exercés dans le groupe d'exercice structuré n'ont pas obtenu un rendement différent, qu'ils aient acquis des tâches complexes ou simples.…”
Section: Résuméunclassified
“…The treatment goal should not necessarily be to provide the most effective performance during therapy, but to organize the therapy session in a way that maximizes proficiency in retention and transfer of the acquired skill (Jarus, 1994). Occupational therapists may use this information when planning treatment.…”
Section: Figurementioning
confidence: 99%